La pluralità funzionale e formativa del modello della ricerca-azione - Travaglini, Roberto (Studi sulla Formazione/Open Journal of Education, 2022)
Adopting the action research method, the researcher, often coinciding with the figure of the teacher, who has become active, builds the programmatic, organizational and evaluative plans of the research, participating as a protagonist, together with the class, in the continuous and unpredictable deviations of path of the investigative project: according to the natural transformative processes – cognitive, emotional, social – of the contingent situation, the researcher can use different models of educational research in a multifunctional way. In spite of the strictly experimental logic, the more empirical logic of action research allows to construct a plastic ecosystemic framework of the socio-environmental situation and to observe it in its entirety and complexity. The epistemological foundations of this research model are dotted with critical elements, which can be largely rethought as strong elements for the overall education of the research actors.